Using SAFMEDS to assist language learners to acquire second-language vocabulary. Issue 2 (2nd July 2016) - Beverley, Michael; Hughes, J. Carl; Hastings, Richard P.
ABSTRACT: SAFMEDS ( S ay A ll F ast M inute E very D ay S huffled) cards, in conjunction with graphing learner's progress, were used as an intervention to teach Welsh vocabulary to second-language learners in 4-year seven classes (12 year olds) in an English medium secondary school in Wales. A further class of children of the same age served as a Waiting List Control (WLC). From the curriculum, 200 words were selected by teachers to be studied during the school term. Children in all classes were given a pretest to establish the number of words that each child already knew at baseline. Children in the four intervention classes were each given packs of Welsh-English SAFMEDS and required to pair up with another child. Both children were instructed to conduct a practice run followed by a 1-min timing at the start of each 50-min lesson (three lessons per week). Children then recorded their correct and incorrect responses on data sheets and graphs. The procedure took less than 5 min, and the teacher then continued with the scheduled lesson. The WLC class received their normal Welsh classes. The intervention spanned 4 weeks of the term and was followed with a post-test of the target words for all children. During the post-test, the intervention children wrote significantly more correct Welsh vocabulary words than the control children, p < .001, d = 1.54. The study demonstrates that SAFMEDS are an efficient and effective method to enhance vocabulary learning with brief exposure within the context of standard lessons.